Low Self-rated Health Is Related to Blood Hypercoagulability in Patients Admitted with Acute Myocardial Infarction - von Känel, Roland; Meister-Langraf, Rebecca E.; Schmid, Jean-Paul; Barth, Jürgen; Znoj, Hansjörg; Schnyder, Ulrich; Princip, Mary (Thrombosis and Haemostasis, 2018)
Self-rated health (SRH) is independently associated with all-cause mortality and adverse cardiovascular outcomes in individuals with and without cardiovascular disease. We examined whether SRH relates to haemostatic factors of a hypercoagulable state with prognostic impact in patients admitted with acute myocardial infarction (MI). We assessed 190 patients (median age: 59 years; all Caucasian; 83% men) within 48 hours of an acute coronary intervention in terms of demographic factors, medical and psychiatric comorbidity, health behaviours, cardiac-related variables and psychosocial characteristics. Patients rated their health state before MI retrospectively with the EuroQol Visual Analogue Scale ranging from 0 (‘worst imaginable health state’) to 100 (‘best imaginable health state’). Circulating levels of fibrinogen, fibrin D-dimer and von Willebrand factor (VWF) antigen were measured the morning after hospital referral. The median score of SRH was 75 (range: 20–100). SRH was inversely associated with fibrinogen (r =  − 0.25, p = 0.001) and D-dimer (r =  − 0.17, p = 0.021) levels in the bivariate analysis. Stronger relationships emerged for fibrinogen (r =  − 0.33, p < 0.001), D-dimer (r =  − 0.25, p = 0.001) and also VWF (r =  − 0.19, p = 0.015) levels in fully adjusted linear regression models. As for SRH, the Global Registry of Acute Coronary Events (GRACE) risk score was the only covariate showing an independent association with all haemostatic factors (fibrinogen: r = 0.31, D-dimer: r = 0.29, VWF: r = 0.30; all p-values < 0.001). Lower SRH was associated with greater coagulability in patients with acute MI, independent of covariates and comparable with the GRACE risk score. The findings provide a novel psychobiological mechanism that may potentially link SRH with cardiovascular outcome in patients with an acute coronary syndrome.
Keywords: cardiovascular diseases; coagulation factors; interoception; psychobiology; psychosocial risk factors